Аdvanced glycation end-products as novel biomarkers of eosinophil-derived lung inflammatory diseases (literature review) - A. Gamian; S.O. Zubchenko; A.M. Havrylyuk; I.Y. Kril; V.V. Chopyak (Medičnì Perspektivi)
Advanced glycation end-products (AGEs) are created during the process of glycation of cells from various tissues and fluids and are a heterogeneous group of molecules formed from the nonenzymatic reaction of reducing sugars with the amino group of proteins, lipids, and nucleic acid. In normal conditions, they play the immunoregulatory role. In pathologic conditions AGEs activate the receptors for advanced glycation end products (RAGE) and cause long-lasting inflammation. RAGE participates actively in various disorders such as rheumatoid arthritis, diabetes, etc. However, there is relatively small number of scientific studies on the possibility of using the role of AGE in the pathogenesis of allergic diseases. RAGE transcript and protein are expressed in the lung by pulmonary type I alveolar epithelial cells, suggesting that RAGE has an important role in lung pathophysiology. They repress some endogenous autoregulatory functions leading to many diseases, including allergy.  Oxidative stress increases the inflammatory reaction in asthma and allergies. Long-lasting inflammation followed by free radicals production are important factors involved in allergic reactions, they negatively influence the incidence and prognosis of allergy. RAGEs are expressed on circulating immune cells, they activate NF kappaB and intracellular oxidative stress also increases the inflammatory reaction in asthma and allergies. The membrane RAGE (mRAGE) signaling is proinflammatory, whereas soluble RAGE (sRAGE), a secreted form of RAGE, is generally anti-inflammatory. The study of AGEs, soluble RAGE, ligands of RAGE HMGB1, and S100A8/A913 and IL-33 is useful in the context of their considering as biomarkers to the differentiation diagnostic between eosinophils-derived and neutrophil-derived asthma/AAD. The mean serum levels of RAGE may be the target of new therapeutic interventions.